Gambaran Dukungan Keluarga Untuk Mengatasi Tingkat Kecemasan Ibu Hamil Primigravida - Ishak, Fifi; Nurdin, St. Surya Indah; Katili, Rusli A (Madu : Jurnal Kesehatan, 2025)
First pregnancy, or primigravida, often became a period filled with anxiety for pregnant women. This anxiety could be influenced by various factors, one of which was family support. Adequate support from family was critical to help pregnant women cope with anxiety during pregnancy, especially in the first, second, and third trimesters. This study aimed to determine the level of family support in overcoming anxiety levels in primigravida pregnant women during the first, second, and third trimesters at Kabila Health Center, Bone Bolango Regency. This study used a descriptive quantitative design. Data were collected through a questionnaire given to 45 primigravida pregnant women registered at Kabila Health Center. The results showed that most respondents who received good family support tended to have lower anxiety levels. Conversely, pregnant women with less family support tended to experience higher anxietyFamily support played an important role in helping to reduce anxiety in primigravida pregnant women. Therefore, it was highly recommended that families actively provide support during pregnancy.